The Use of Electronic Gadgets by the Preschool Children: An Exploration of Mothers’ Knowledge and Perception - Ranabhat, Apsara; Lamichhane, Sabina (Academia Journal of Humanities & Social Sciences, 2026)
The preschool children are increasingly exposed to the digital devices such as smartphones, tablets, television, and computers at an early age. This may lead to the health problems and technology addiction. This study aimed to assess the awareness and perceptions of mothers regarding the use of electronic gadgets by their children in a community in Pokhara Metropolitan City, Kaski, Nepal. A community-based descriptive cross-sectional study was conducted among 216 mothers of children aged 3-5 years through a purposive sampling technique. Data were collected through the face-to-face interviews, using the structured questionnaires and analyzed using SPSS version 16. Descriptive statistics and the chi-square test were applied to assess the associations between the selected variables and the level of awareness and perception. The results showed that most mothers (64.8%) had a poor level of awareness and 51.9% had a negative perception toward the children’s use of electronic gadgets. A statistically significant association was observed between the level of awareness and the age of the child (p = 0.029) as well as the number of hours spent using the gadgets (p = 0.039). The findings of the study revealed that most mothers had poor awareness of the electronic gadget use among the preschool children, although nearly half of them perceived positively. The awareness programs and parental education are essential to promote the safe and effective gadget use among the preschool children.